Analysis of Prenuptial Agreements in the Qur'an: A Feminist Interpretation Study in Addressing Gender Bias and Gender Justice - Wahyu Muhammad Abdul Wahid; Reyazul Jinan Haikal; Eni Zulaiha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
A prenuptial agreement is a contract signed by the bride and groom before marriage to legally establish them as husband and wife. As a contract, this agreement binds both parties and can include provisions regarding the division of property or management of personal assets, so that each party can be separated in the event of a future separation. This study uses a qualitative research method, with a descriptive-analysis technique. Data collection was carried out using a literature study approach. Based on the study conducted, the following are the results of the study. First, Buya Hamka's interpretation of QS. Al-Maidah verse 1, falls into the category of gender-biased interpretation. This can be seen from his interpretation having a tendency towards one of the parties. Second, the feminist or gender-just interpretation of QS. Al-Maidah verse 1, is more oriented towards more just values, especially across genders.